The Relationship of Dyadic Coping With Emotional Functioning and Quality of the Relationship in Couples Facing Cancer—A Meta-Analysis - Ştefǎnuţ, Adelina Mihaela; Vintilǎ, Mona; Tudorel, Otilia Ioana (Frontiers in Psychology, 2021)
Objective: This study is a meta-analysis that considers the association between dyadic coping and emotional well-being, and between dyadic coping and the quality of the relationship as perceived by cancer patients and their life partners. Methods: A systematic search was conducted in the electronic databases PsycINFO, PubMed, ScienceDirect and those peer-reviewed cross-sectional and longitudinal studies published up until April 2020 that investigated these relationships were selected. Results: A total of 1161 studies were identified, of which 10 met the inclusion criteria (N=1727 couples). These evidenced statistically significant positive relationships between common dyadic coping and emotional well-being and between common dyadic coping and the quality of the relationship as perceived by patients and their partners. There was also a statistically significant positive association between stress communication (by oneself), supportive dyadic coping (by oneself and by partner), and the quality of the relationship. In addition, a statistically significant negative association was found between negative dyadic coping (by oneself and by partner) and the quality of the relationship as perceived by patients' partners and also between negative dyadic coping (by oneself) and the quality of the relationship as perceived by patients. Conclusions: The results suggest the existence of a significant association between dyadic coping and emotional well-being and between dyadic coping and the quality of the relationship as perceived by members of couples facing cancer. However, these results must be interpreted with caution due to the small number of studies included in the analysis. Clinically, an understanding of the existence of such relationships is helpful for the implementation, and study of the effectiveness of, interventions aimed at improving dyadic coping in order to improve both quality of life and quality of relationship in couples where there is an oncological diagnosis.